Application of Nanotechnology for Water Treatment - Dr. Bikram Keshari Das; Dr. Tanushree Das; Miss Surekha Majhi; Mrs. Dipteerekha Das (Application of Nanotechnology for Water Treatment, Edition 1, 2025)
Water contamination is a growing global concern, necessitating advanced treatment strategies to ensure clean and safe water. Nanotechnology offers promising solutions by providing the unique properties of nanomaterials to enhance water purification efficiency. This book explores fundamental aspects of nanomaterials, including metal nanoparticles, metal oxide nanoparticles, carbon-based nanomaterials, and nanocomposites, along with their synthesis and functionalization by using top-down and bottom-up approaches. Key topics include adsorption mechanisms, photocatalysis, and membrane-based technologies for removing heavy metals, organic pollutants, pathogens, and emerging contaminants. The improved efficiency, effectiveness, and flexibility of nano-enabled water treatment are highlighted by compared to traditional approaches. The book also addresses economic feasibility, environmental impact, regulatory considerations, and public acceptance of nanotechnology-driven solutions. Public perception and acceptance of nanotechnology-based solutions are analyzed to assess scalability and real-world implementation. The book concludes with an overview of existing challenges such as nanoparticle stability, regeneration, and safe disposal while outlining future trends in nano-enabled water treatment, including hybrid nanomaterial systems, bio-inspired nanotechnologies, and AI-driven optimization. This book aims to solve current challenges and provide next-generation treatment options for global water security by expanding nanotechnology applications and supporting sustainable water purification techniques.